Apakah Cinta pada Uang Berpengaruh Terhadap Tindakan Kecurangan pada Organisasi Nirlaba? - Anggrayni, Lilly; Azzochrah, Nurul Azizah; Niu, Fitria Ayu Lestari (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This research examine the effect of love of money variable on fraud action, which is related with the issue of fraud accounting. Love of money is founded had partial effect to the fraud action, this is proved by the data that love of money had R2 as many as 13,7%, which means that love of money had partial effect to fraud action which is only about 13,7 % and the rest value could effect by the other variable. This research adopt agency theory as the main theory which could frame the relation between love of money variable and fraud action variable. Love of money is defined as the motivation or desire to reach money in human life. This intention exist because human had natural ego behavior such as want to owning assets, power, and self-expression and the other people in the society also think that money is the reflection of social status as well as reflected their achievement. This motivation could boost volunteers and managers desire to commit fraud action in non-profit organizations. This finding is in line with agency theory, which state that people had possibility to take self-interest when they had power and access to control and manage resources in an organizations. Manager and volunteers had access and authority to the financial resources in the organizations, therefore they had chance to take self-interest. This action could happend if the organization had lack of monitoring systems, and society did not push the organizations to report their operational, program and financial activity.